(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper presents the implementation of Incremental Conductance (IC) Maximum Power Point Tracking (MPPT) for photovoltaic (PV) system integrated with a DC-DC boost converter to enhance energy harvesting efficiency. Output power varies with environmental conditions such as solar irradiance and temperature due to the nonlinear characteristics of PV modules. To address this challenge, The IC MPPT technique is employed to accurately track the maximum power point (MPP) under both steady-state and rapidly changing environmental conditions. Unlike conventional methods, the incremental conductance approach determines the MPP by comparing IC ( with the instantaneous conductance (), reduced oscillations and improved tracking speed. The proposed system consists of a PV array, an IC based MPPT controller and a boost converter that steps up the output voltage to a required level for efficient load utilization. The boost converter is controller through pulse width modulation (PWM) signals generated by the MPPT algorithm, enabling optimal power extraction from the PV panel. MATLAB/Simulink is used to model and simulate the system, validating its performance under varying irradiance conditions. Simulation outcome indicates that the IC MPPT technique achieves improved efficiency, quicker tracking of MPP and minimizes steady-state fluctuations when compared to conventional approaches like Perturb and Observe (P&O) method. The system ensures reliable and stable operation, making it suitable for renewable energy applications. Overall, the integration of the IC MPPT with a boost converter significantly improves the performance and efficiency of photovoltaic energy systems.